A UV light-responsive amphiphilic block copolymer and its preparation and application

UV photoresponsive amphiphilic block copolymers were prepared by RAFT polymerization technology, forming nano micelles and encapsulating doxorubicin, solving the problems of background signal interference and low proton sensitivity in the existing 1H MRI technology, achieving high contrast imaging and drug controlled release of 19F MRI, with non-toxic and targeted controlled release characteristics.

CN115819693BActive Publication Date: 2025-04-18QINGDAO UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211679599.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-27
Publication Date
2025-04-18
Estimated Expiration
2042-12-27

AI Technical Summary

Technical Problem

The existing 1H MRI technology has background signal interference, low proton sensitivity and potential health risks brought by contrast agents, making it difficult to achieve high contrast and early disease diagnosis.

Method used

The preparation of the 19F MRI diagnostic and treatment probe was achieved by using RAFT polymerization technology to prepare UV photoresponsive amphiphilic block copolymer, forming nano micelles and encapsulating the anti-cancer drug doxorubicin. This probe can achieve accurate and controlled release of drugs under UV light stimulation.

Benefits of technology

The high contrast imaging and controlled drug release of 19F MRI are achieved, avoiding the toxicity risk of traditional MRI contrast agents, and have the characteristics of non-toxic and targeted controlled release, which is suitable for biopharmaceutical loading and imaging detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115819693B_ABST
    Figure CN115819693B_ABST
Patent Text Reader

Abstract

The present invention discloses a UV light-responsive amphiphilic block copolymer and a preparation method thereof. The structure of the photoresponsive amphiphilic block copolymer is shown in Formula I, wherein m is an integer between 5 and 100, and n is an integer between 100 and 200. The present invention also discloses UV light-responsive amphiphilic block copolymer micelles and drug-loaded micelles prepared according to the amphiphilic block copolymer. The drug-loaded micelles can release drugs under the action of UV light to achieve precise and controllable drug release. 19 F MRI diagnostic probe provides design ideas, theoretical guidance and technical support. #imgabs0#
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nuclear magnetic resonance imaging, and specifically relates to a UV light responsive amphiphilic block copolymer, a preparation method, and a method for preparing the same. 19 F Application of MRI diagnostic probes. Background Art

[0002] Magnetic resonance imaging (MRI) has the characteristics of high spatial resolution and no ionizing radiation. It is an emerging imaging method that uses magnetic resonance phenomena to obtain electrical signals. Currently, most of the commonly used MRIs in clinical practice are 1 H MRI is affected by the background signal of normal tissues and has the problem of low proton sensitivity. 1 H MRI usually requires contrast agents to increase contrast and improve imaging effects. Proton contrast agents are divided into T1 and T2 contrast agents. T2 contrast agents are iron-based nanomaterials, which are negative contrast agents and are easily interfered by endogenous iron or blood clots in the human body, leading to misjudgment. The mainstream T1 contrast agent is gadolinium-based contrast agent, which is easy to cause brain deposition, nephrogenic systemic fibrosis and other diseases.

[0003] 19 F MRI is a potential MRI. 1 H MRI, 19 F MRI has the advantages of high natural abundance, chemical shift being more sensitive to the local tissue environment, and almost no endogenous background interference. It can obtain clearer MRI images for early diagnosis of diseases. 19 The application of F MRI is to overcome 1 One of the promising strategies for H MRI limitation is that the fluorine content in human tissue is very low (negligible). 19 F MRI signals come only from the fluorine atoms it contains, which will maximize the contrast of the image. Compared with the standard paramagnetic substances (gadolinium, etc.), another advantage of fluorinated contrast agents is their non-toxicity and stability, without the risk of decomposition or release of toxic metal ions. Based on this, the development of high-quality 19 F MRI molecular probes have far-reaching significance for MRI diagnosis.

[0004] Controlled drug delivery systems (CDDS) overcome many problems of traditional drug delivery systems (such as low utilization, poor selectivity, sustained release, etc.) and achieve controllable, efficient and rapid release of drugs at the tumor site. This "smart material" can respond to stimulation from the internal environment of the organism (such as pH, redox, enzymes, etc.) or the external environment (temperature, electricity / magnetism, ultrasound, light, etc.). Among them, light is a clean, non-invasive and effective stimulus source that can achieve high-concentration drug release at the lesion site by adjusting wavelength, intensity, time and space. Photosensitive groups (such as o-nitrobenzyl oxygen) can absorb photon energy in photolysis-type drug delivery systems, resulting in the breaking of specific covalent bonds. Under ultraviolet (UV) or near-infrared (NIR) irradiation, drug release by inducing structural changes has been widely used and verified to be an ideal optical controlled release method.

[0005] The present invention utilizes reversible addition-fragmentation chain transfer (RAFT) polymerization technology, which has the advantages of narrow molecular weight distribution, controllable "activity" and strong molecular design capability, to prepare UV light-responsive fluorinated amphiphilic block polymer poly(ethylene glycol) (PEG 100 )-o-nitrobenzyloxy-poly(2,2,2-trifluoroethylacrylate)(PEG 100 -oNB-b-PTFEA 5-100 ), self-assembled in aqueous solution to form nanomicelles, and the hydrophobic anticancer drug doxorubicin (DOX) was successfully encapsulated in the micelle core. This diagnostic and therapeutic probe can meet the needs of both imaging and drug controlled release, and is simple to prepare with high repeatability, providing design ideas, theoretical guidance and technical support for "intelligent" diagnostic and therapeutic probes that integrate controllable stimulus response, excellent imaging signals, low biological toxicity and good drug loading capacity. Summary of the invention

[0006] One object of the present invention is to provide a UV light responsive amphiphilic block copolymer and a preparation method thereof. Another object of the present invention is to provide a UV light responsive amphiphilic block copolymer micelle prepared according to the amphiphilic block copolymer. Another object of the present invention is to provide a UV light responsive amphiphilic block copolymer micelle in the preparation of 19 Application of FMRI diagnostic probes.

[0007] In a first aspect, the present invention discloses a UV light-responsive amphiphilic block copolymer, characterized in that the structure of the photoresponsive amphiphilic block copolymer is as shown in Formula I:

[0008]

[0009] Wherein, m is an integer between 5 and 100, including but not limited to 5, 10, 20, 30, 50, and 100.

[0010] n is an integer between 100-200. In the most preferred embodiment of the present invention, n is 100.

[0011] In a second aspect, the present invention provides a method for preparing a UV light-responsive amphiphilic block copolymer, the method comprising the following steps:

[0012] (1) 4-Hydroxymethyl-3-nitrobenzoic acid and 1-hydroxypyrrolidine-2,5-dione are mixed, activated by carbodiimide, and stirred at room temperature to obtain 2,5-dioxypyrrolidine-1-yl 4-(hydroxymethyl)-3-nitrobenzoic acid;

[0013] (2) 2,5-dioxypyrrolidin-1-yl 4-(hydroxymethyl)-3-nitrobenzoic acid and 2-((butyl)carbonyl)thio)propionic acid are dissolved in an organic solvent and reacted at 0-5° C. to obtain methyl 2,5-dioxypyrrolidin-1-yl 3-nitro-4-((2-((propylthio)carbonylthio)propionyl)oxy)benzoate;

[0014] (3) 2,5-dioxypyrrolidin-1-yl 3-nitro-4-((2-((propylthio)carbonylthio)propionyl)oxy)benzoic acid methyl ester and NH2-PEG100 are dissolved in an organic solvent and reacted overnight under alkaline conditions to obtain a RAFT chain transfer agent. The structural formula of the NH2-PEG100 is as follows:

[0015]

[0016] The structure of the RAFT chain transfer agent is shown in Formula II:

[0017]

[0018] (4) In an inert gas, AIBN is used as an initiator, TFEA, a RAFT chain transfer agent, and AIBN are dissolved in an organic solvent at a molar mass ratio of m:1:0.1, and the mixture is stirred at 70-75°C for 12-24 hours to obtain a UV light responsive amphiphilic block copolymer, wherein m is an integer between 5 and 100, and the structure of the UV light responsive amphiphilic block copolymer is shown in Formula III.

[0019]

[0020] The TFEA of the present invention refers to the structural formula of compounds.

[0021] Preferably, m in step (4) includes 5, 10, 20, 30, 50, 100. In the most preferred embodiment of the present invention, m is 5 or 10.

[0022] The organic solvent described in the above preparation method includes one or a combination of two or more of DMF, dichloromethane, chloroform, DMSO and acetone.

[0023] Preferably, the alkaline conditions in step (3) include adding a basic solvent selected from the group consisting of triethylamine and ethylenediamine to an organic solvent.

[0024] In a third aspect, the present invention provides a UV light-responsive amphiphilic block copolymer micelle, characterized in that the copolymer micelle is obtained by self-assembly of the above-mentioned UV light-responsive amphiphilic block copolymer in an aqueous solution.

[0025] In a fourth aspect, the present invention provides a UV light-responsive amphiphilic block copolymer drug-loaded micelle, characterized in that the copolymer drug-loaded micelle is prepared by the following method: dissolving the drug and the UV light-responsive amphiphilic block copolymer in a solvent respectively, mixing, stirring the reaction overnight, and dialyzing to obtain the UV light-responsive amphiphilic block copolymer drug-loaded micelle.

[0026] The drug is a compound having a therapeutic effect on a disease, including but not limited to doxorubicin (DOX).

[0027] In a fifth aspect, the present invention provides a photoresponsive amphiphilic block copolymer, a UV photoresponsive amphiphilic block copolymer micelle, and a UV photoresponsive amphiphilic block copolymer drug-loaded micelle. 19 Application of fMRI as diagnostic and / or therapeutic probes.

[0028] The present invention adopts the RAFT polymerization reaction principle to prepare a hydrophilic UV light-responsive macromolecular RAFT chain transfer agent with a stable structure and properties, and then prepares an amphiphilic block copolymer through RAFT polymerization. The amphiphilic block copolymer can achieve drug encapsulation through self-assembly, and release the drug under the action of photodecomposition of the o-nitrobenzyl group by utilizing the light stimulus-response characteristics, so as to achieve the purpose of accurately and controllably releasing the drug. 19 F MRI imaging provides conditions for studying the release process of drugs, making it widely used in biological drug delivery, imaging, detection, etc., achieving characteristics such as no toxic side effects and targeted controlled release. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Diagram of the drug release process of UV light-responsive amphiphilic block copolymer drug-loaded micelles.

[0030] Figure 2 UV / Vis absorption spectra of photoresponsive block copolymers P1 and P2.

[0031] Figure 3 Particle size distribution of blank micelles (solid line) and DOX-loaded micelles (dashed line).

[0032] Figure 4 TEM images of polymer micelles before (blank micelles (a) and DOX-loaded micelles (b)) and after (blank micelles (c) and DOX-loaded micelles (d)) UV irradiation.

[0033] Figure 5 Stability of blank micelles (solid line) and drug-loaded micelles (dashed line) in PBS (pH=7.4) buffer at 37°C over time (the curves from top to bottom represent the monitoring time increasing gradually). Data represent the mean and standard deviation of three independent experiments.

[0034] Figure 6 Blank micelles P2B and drug-loaded micelles P2B&DOX were exposed to UV light (1-15 min) or without UV light (0.196 W / cm 2 , 320-480nm) conditions.

[0035] Figure 7 The drug-loaded micelles were exposed to UV light (20 min) or without UV light (0.196 W / cm 2 , 320-480nm) conditions.

[0036] Figure 8 Nanoparticles 19 F NMR and 19 F MRI; a) Blank micelles in vitro 1 H and 19 F MRI image; b) blank micelle 19 F NMR spectrum (the right side of the micelle peak is the trifluoroacetic acid calibration peak).

[0037] Fig. 9 The viability of HUVEC cells after incubation with blank micelles of different concentrations for 48 hours (PIB on the left and P2B on the right).

[0038] Fig.10 Survival rate of HUVEC cells after incubation with different concentrations of blank micelles (P2B) and their degradation products for 48 h (P2B on the left and degradation products on the right). DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, not all. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1 Preparation of UV light responsive amphiphilic block copolymer

[0041] The preparation flow chart is as follows:

[0042]

[0043] S1: Preparation of o-nitrobenzyl derivatives

[0044] (1) Preparation of 4-(hydroxymethyl)-3-nitrobenzoic acid

[0045] 4-(Bromomethyl)-3-nitrobenzoic acid (1.01 g, 3.88 mmol) and sodium carbonate (2.68 g, 13.6 mmol) were dissolved in water / acetone (1:1 (v / v), 30 mL) and refluxed for 5 h. The acetone was evaporated and the aqueous phase was extracted with ether (2×15 mL). Dilute hydrochloric acid was added dropwise until the pH value was below 1 to form a yellow precipitate. Ethyl acetate (2×20 mL) was added to redissolve it. The aqueous phase was extracted with ethyl acetate (3×20 mL). The organic phase was washed with water (2×20 mL), dried over magnesium sulfate, and evaporated to dryness under reduced pressure (98%) to obtain a slightly yellow powder product.

[0046] (2) Preparation of 2,5-dioxypyrrolidin-1-yl 4-(hydroxymethyl)-3-nitrobenzoic acid

[0047] 4-Hydroxymethyl-3-nitrobenzoic acid (1.00 g, 5.07 mmol) and 1-hydroxypyrrolidine-2,5-dione (702 mg, 6.08 mmol) were dissolved in DMF (15 mL), EDCI-HCI (1.16 g, 6.08 mmol) was added, and the mixture was stirred at room temperature for 2 h. Water was added, and the mixture was extracted with ethyl acetate three times. The organic layer was washed with 2.8% potassium hydrogen sulfate and brine, dried over anhydrous sodium sulfate, concentrated in vacuo, purified by silica chromatography, and dried in vacuo to obtain a yellow powder product.

[0048] (3) Preparation of PABTC-oNB

[0049] 2,5-Dioxopyrrolidin-1-yl 4-(hydroxymethyl)-3-nitrobenzoic acid (0.323 g, 0.90 mmol, 1.00 eq), 2-((butyl)carbonyl)thio)propionic acid (0.69 g, 2.88 mmol, 2.62 eq) and DMAP (0.03 g, 0.23 mmol, 0.21 eq) were dissolved in 10 ml of dry DCM. The solution was cooled to 0°C under ice bath conditions. Then 0.85 g of EDC hydrochloride was added in proportion. After stirring for 7 h, 0.1 g of EDC hydrochloride (total amount of EDC hydrochloride: 0.95 g, 4.94 mmol, 4.50 eq) was added. After stirring for 24 h, the mixture was diluted with 20 ml of EA, and 20 ml of 0.5 M HCL and 20 ml of 0.1 M The mixture was washed twice with NaHCO3 and 25 ml NH4Cl, and the solvent was removed under reduced pressure. The product was purified by column chromatography in cyclohexane / EA (95 / 5-3 / 2) and dried in vacuo to give a yellow oil, namely methyl 2,5-dioxopyrrolidin-1-yl 3-nitro-4-((2-((propylthio)carbonylthio)propionyl)oxy)benzoate (PABTC-oNB).

[0050] S2: Synthesis of RAFT chain transfer agent (RAFT-oNB-PEG)

[0051] Methyl 2,5-dioxopyrrolidin-1-yl 3-nitro-4-((2-((propylthio)carbonylthio)propionyl)oxy)benzoate (2.2 mg, 4.2 μmol) and 2-methoxyethyl (2-aminoethyl)carbamate (NH2-PEG100) (0.49 mg, 2.1 μmol) and triethylamine (0.85 mg, 8.4 μmol) were dissolved in 57 ml of dimethyl sulfoxide, and the mixture was reacted at room temperature overnight. The product was first purified by precipitating in ether three times, and then vacuum dried to obtain a light yellow powder.

[0052] S3: Synthesis of UV-responsive amphiphilic block copolymers

[0053] First, the polymerization ratio was determined to be monomer: initiator: RAFT agent = 5: 0.1: 1. According to the feed ratio, the theoretical degree of polymerization in the polymer was 5. The specific operation was as follows: AIBN was used as the initiator, TFEA, RAFT-oNB-PEG, and AIBN were added to 3 ml of DMF solution at a ratio of 5 / 1 / 0.1, and then placed in a 10 mL reaction tube, and the reaction tube was sealed with a rubber stopper. The gas in the reaction system was removed by vacuum freeze thaws (vacuum freeze thaws), and finally inert gas nitrogen was introduced. The reaction was stirred at 70 ° C for 24 hours. After the reaction was completed, the product was loaded into a dialysis bag with a molecular weight of 3500, and 2000 ml of deionized water was added to the beaker for dialysis for 48 hours, and the deionized water was replaced every 4 hours, 6 hours, 8 hours, and 12 hours to remove the DMF solution and impurities in the system. Finally, the photoresponsive block polymer PEG was obtained by freeze drying in a freeze dryer. 100 -oNB-b-PTFEA5.

[0054] According to the same method, AIBN was used as the initiator, and TFEA, RAFT-oNB-PEG, and AIBN were mixed in a ratio of 10 / 1 / 0.1 to prepare the photoresponsive block polymer PEG. 100 -oNB-b-PTFEA 10 .

[0055] Example 2 Preparation of UV light-responsive amphiphilic block copolymer drug-loaded micelles

[0056] UV light responsive amphiphilic block copolymer PEG synthesized by the above method 100 -oNB-b-PTFEA5、PEG 100 -oNB-b-PTFEA 10 The present invention can self-assemble into micelles in aqueous solution. The blank micelles and DOX-loaded micelles are prepared by dialysis. The specific method is as follows: DOX·HCl (5 mg) is accurately weighed and dissolved in DMSO (1 mL), and then three molar equivalents of triethylamine (TEA) (MW = 101.1, ρ = 0.728) are added and stirred for 4 hours to obtain DOX alkali solution. The polymer PEG is accurately weighed 100 -oNB-b-PTFEA5 and PEG 100 -oNB-b-PTFEA 1050 mg of each was dissolved in DMSO (1 mL) and stirred until completely dissolved. Then, DOX alkali solution was added and stirred overnight. The mixture was added dropwise to ultrapure water (15 mL) under vigorous stirring using a constant pressure funnel. The mixture was transferred to a dialysis bag (molecular weight cutoff (MWCO = 3.5 KDa) and dialyzed in ultrapure water for 24 hours (ultrapure water was replaced every 4 hours) to remove DMSO and free DOX. After the dialysis, the drug-loaded nanomicelles were obtained by filtration through a filter membrane (0.45 μm) and freeze-dried.

[0057] Example 3 Preparation of UV light-responsive amphiphilic block copolymer micelles

[0058] The UV light-responsive amphiphilic block copolymer micelles, referred to as blank micelles, were prepared in the same manner as in Example 2, except that they were prepared using the same procedure in the absence of DOX drug.

[0059] Effect verification

[0060] In the following experiments, the present invention uses UV light responsive amphiphilic block copolymer PEG 100 -oNB-b-PTFEA5、PEG 100 -oNB-b-PTFEA 10 The blank micelles prepared from P1 and P2 by dialysis were named P1B and P2B, and the micelles loaded with DOX were named P1&DOX and P2&DOX.

[0061] (1) UV / Vis absorption spectra of P1 and P2

[0062] The UV-Vis absorbance of the photosensitive polymers was monitored by a UV-Vis spectrometer (Hitachi U-4100, Japan). 0.075 mg / mL polymer solutions (P1 and P2) were prepared in DCM and exposed to UV irradiation (0.196 W / cm 2 , 320-480nm) in a specific time period (5-1200s). The results are as follows Figure 2 As shown, the curve from top to bottom indicates that the illumination time is extended. The left figure shows the UV / Vis absorption spectrum of P1, and the right figure shows the UV / Vis absorption spectrum of P2. It can be seen from the figure that the absorbance of P1 and P2 at 310nm is significantly reduced, which is consistent with the decomposition of the oNB group.

[0063] (2) Determination of the particle size of drug-loaded nanomicelles

[0064] The particle size of P1B and P2B, P1&DOX and P2&DOX prepared by the present invention was measured by dynamic light scattering (DLS). DLS measurement was performed using a Zetasizer Nano ZS90 instrument from Malvern. The instrument was equipped with a 4.0mW He-Ne laser, an operating wavelength of 633nm, and a detection angle of 173°. The intensity-weighted average hydrodynamic diameter (Z average value) and the polydispersity factor were obtained by analyzing the autocorrelation function using the cumulant method. Before starting the measurement, each sample was measured at least three times at 25°C with an equilibrium time of 2 minutes.

[0065] The results are as follows Figure 3 As shown in the figure, all nanoparticles are below 100 nm, which has the potential for passive targeting. The particle size increases with the length of the hydrophobic chain, and all nanoparticle size distributions are normally distributed, indicating that the nanostructure is monodisperse. Compared with the blank nanomicelles, the particle size of the loaded DOX increases slightly, but the particle size distribution remains unchanged, indicating that DOX is effectively filled into the micelles and increases the particle size to a certain extent.

[0066] (3) TEM detection

[0067] Nanomicelles were observed using a JEM2100 electron microscope at an accelerating voltage of 200 kV (photolysis conditions: UV 0.196 W / cm 2 , 320-480nm, 15min). An appropriate amount of polymer solution (blank micelle concentration in PBS was 1mg / mL, pH 7.4) was dropped onto a 400-mesh carbon-supported copper grid, and excess solution was removed with filter paper. The test was performed after evaporation for 24 hours at room temperature in the dark.

[0068] The results are as follows Figure 4 As shown, P2B has a "core-shell" spherical structure with a size of about 40nm. The size of the drug-loaded nanomicelles (P2&DOX) is about 50nm, and there are black spots scattered in the core of the particles, indicating the successful loading of the drug DOX. At the same time, after ultraviolet light irradiation, the structures of the blank nanomicelles and the DOX-loaded nanomicelles are destroyed, and the DOX carried is released in a controlled manner.

[0069] (4) Stability test

[0070] The blank micelles P2B and the micelles P2&DOX loaded with DOX prepared by the present invention were dispersed in a 37°C PBS buffer solution with a pH of 7.4, and the particle size change and PDI were measured by a dynamic light scattering (DLS) instrument. Figure 5As shown, the particle size changes of blank micelles P2B and drug-loaded micelles P2&DOX are basically stable, remaining at about 40 nm in a buffer solution of pH = 7.4 within 5 days, and the PDI remains below 0.4 within 15 days, which indicates that the nanomicelles have good stability in a physiological environment.

[0071] (5) PCS count rate after irradiation of drug-loaded nanomicelles

[0072] The blank micelles P2 and the micelles P2&DOX loaded with DOX prepared in the present invention were dispersed in PBS buffer (pH=7.4) and irradiated with UV light (0.196 W / cm 2 , 320-480nm, 15min), the control group was not irradiated with UV light, and the changes in PCS count rate of each group after irradiation were detected by dynamic light scattering (DLS). Figure 6 As shown in the figure, it can be seen that the count rate change of the blank and drug-loaded micelles is significantly reduced within 15 minutes of UV light irradiation, and the nanostructure is degraded by about 50%. The count rate change curve of the control group is relatively flat, indicating that the prepared light-responsive drug-loaded system has obvious stability and photodecomposition characteristics.

[0073] (6) Drug release rate detection of drug-loaded nanomicelles

[0074] The drug release rate of DOX-loaded polymer nanomicelles was determined using a fluorescence spectrophotometer (Hitachi U-4100). The freeze-dried DOX-loaded polymer nanomicelles (5 mg) were accurately weighed and dispersed in PBS buffer (5 mL, pH = 7.4). After stabilization for 30 minutes, they were transferred to a dialysis bag (MWCO = 3.5 KDa), and then placed in 95 mL PBS buffer and released in vitro in a constant temperature shaker (37 ° C, 100 rpm). The external solution (4 mL) of the dialysis bag was taken at a specific time point and supplemented with the same new buffer (4 ml). The DOX content in the released solution was measured by a fluorescence spectrophotometer. The results are shown in Figure 2. Figure 7 As shown, without UV light irradiation, the cumulative release of DOX after 48 hours was only 19.80%, indicating that the DOX-loaded NPs have relatively good stability under normal physiological conditions (such as blood). The hydrophobic core of NPs keeps DOX molecules accumulated and locked inside NPs. In contrast, under 30 minutes of UV irradiation, the cumulative release of DOX was twice that of non-UV irradiation, reaching 46.3% after 48 hours, which is basically consistent with the results of PCS count rate.

[0075] (7) In vitro 1 H and 19 F MRI imaging

[0076] In equipped with 1 H / 19 F Dual Probe (RF RES 1 H / 19 MRI tests were performed on a 7.0T 200mm lateral bore microscopy system (Bruker BioSpec 70 / 20USR) with a FLASH sequence. 19 F MRI image, set parameters are TR / TE=800 / 1.3ms, FA=30.0, FOV=40*40mm, MTX=32, average value=20. Acquired using RARE sequence 1 H MRI image, the parameters were set as TR / TE=2000 / 33ms, FA=180.0, FOV:40*40m, MTX=256, average value=20. Two drug-loaded nanomicelles with different hydrophobic segment lengths were dispersed in PBS (pH=7.4) buffer ( 19 The solvent for F NMR was D2O) at a concentration of 10 mg / mL. 1 H and 19 F MRI imaging, the results are as follows Figure 8 As shown in a, it can be seen that the two blank micelles 1 H and 19 F MRI imaging showed good imaging capabilities. Figure 8 b is 19 F NMR test results, it can be seen from the figure that all 19 The F NMR spectrum showed a single spectral line and a sharp single peak at -75.51 ppm, indicating that the nanomicelles had good imaging sensitivity.

[0077] (8) Cytotoxicity detection of blank nanomicelles

[0078] The toxicity of blank micelles (P1B and P2B) to HUVEC cells was detected by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) staining. First, cells were inoculated and the cells in the logarithmic growth phase were set to 8 concentrations and 4 multiwells. The cells were inoculated in a 96-well plate (100 μL / well, 3000 / well). They were cultured in a carbon dioxide incubator. The next day, samples (1.56-100 μM) were prepared and a 0 μM control group was set. The old culture medium was removed from the 96-well plate and the sample was added at a rate of 100 μL / well. Then culture was carried out in a carbon dioxide incubator. After 24 hours, MTT (5 mg / mL) was added at 10 uL / well and then incubated in a carbon dioxide incubator. After 4 h, the supernatant was removed from the 96-well plate and DMSO was added at a rate of 100 μL / well. After wrapping with tin foil, oscillate for 10 minutes to fully melt the crystals. The absorbance of each well was measured at 490 nm on an ELISA. Fig. 9 After 48 hours of culture, even when the concentration of blank micelles (P1B and P2B) reached 100 μM, the cell viability of HUVEC was still higher than 90%, indicating that the prepared drug-loaded micelles had good biocompatibility.

[0079] (9) Cell killing effect of drug-loaded nanomicelles

[0080] The MTT activity of the degradation products of blank micelle P2B was detected by UV irradiation (0.196 W / cm 2 , 320-480nm, 30min) and then the same procedure as the above cytotoxicity test was performed. Fig.10 As shown in the figure, the survival rate of HUVEC cells after photodegradation remained at the same level. When the concentration reached 100 μM, the survival rate of HUVE cells was still higher than 90%. This shows that the degradation products are also non-biotoxic.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A UV light responsive amphiphilic block copolymer, characterized in that: The structure of the photoresponsive amphiphilic block copolymer is shown in Formula I: Wherein, m is an integer between 5-100, and n is an integer between 100-200.

2. The UV light-responsive amphiphilic block copolymer according to claim 1, characterized in that The m is selected from 5, 10, 20, 30, 50 or 100, and the n is 100.

3. A method for preparing the UV light responsive amphiphilic block copolymer according to claim 1, the method comprising the following steps: (1) 4-Hydroxymethyl-3-nitrobenzoic acid and 1-hydroxypyrrolidine-2,5-dione are mixed, activated by carbodiimide, and stirred at room temperature to obtain 2,5-dioxypyrrolidine-1-yl 4-(hydroxymethyl)-3-nitrobenzoic acid; (2) 2,5-dioxypyrrolidin-1-yl 4-(hydroxymethyl)-3-nitrobenzoic acid and 2-((butyl)carbonyl)thio)propionic acid are dissolved in an organic solvent and reacted at 0-5° C. to obtain methyl 2,5-dioxypyrrolidin-1-yl 3-nitro-4-((2-((propylthio)carbonylthio)propionyl)oxy)benzoate; (3) 2,5-dioxypyrrolidin-1-yl 3-nitro-4-((2-((propylthio)carbonylthio)propionyl)oxy)benzoic acid methyl ester and NH2-PEG100 are dissolved in an organic solvent and reacted overnight under alkaline conditions to obtain a RAFT chain transfer agent. The structural formula of the NH2-PEG100 is as follows: The structure of the RAFT chain transfer agent is shown in Formula II: (4) In an inert gas, AIBN is used as an initiator, TFEA, a RAFT chain transfer agent, and AIBN are dissolved in an organic solvent at a molar mass ratio of m:1:0.1, and the mixture is stirred at 70-75°C for 12-24 hours to obtain a UV light responsive amphiphilic block copolymer, wherein m is an integer between 5 and 100, and the structure of the UV light responsive amphiphilic block copolymer is shown in Formula III.

4. The preparation method according to claim 3, characterized in that: The m in step (4) includes 5, 10, 20, 30, 50 or 100.

5. The preparation method according to claim 4, characterized in that: The m is 5 or 10.

6. The preparation method according to claim 3, characterized in that: The organic solvent described in the preparation method includes one or a combination of two or more of DMF, dichloromethane, chloroform, DMSO and acetone.

7. The preparation method according to claim 3, characterized in that: The alkaline conditions in step (3) include adding a basic solvent selected from the group consisting of triethylamine and ethylenediamine to an organic solvent.

8. A UV light-responsive amphiphilic block copolymer micelle, characterized in that: The copolymer micelle is obtained by self-assembling the UV light-responsive amphiphilic block copolymer according to claim 1 in an aqueous solution.

9. A UV light-responsive amphiphilic block copolymer drug-loaded micelle, characterized in that: The copolymer drug-loaded micelles are prepared by the following method: dissolving the drug and the UV light-responsive amphiphilic block copolymer according to claim 1 in a solvent respectively, mixing, stirring and reacting overnight, and dialyzing to obtain UV light-responsive amphiphilic block copolymer drug-loaded micelles.

10. A method for preparing the photoresponsive amphiphilic block copolymer of claim 1, the UV photoresponsive amphiphilic block copolymer micelle of claim 8, or the UV photoresponsive amphiphilic block copolymer drug-loaded micelle of claim 9. 19 F MRI diagnostic and / or therapeutic probe applications.

Citation Information

Patent Citations

  • Preparation of cross linker for synthesizing amphipathic gel and application of the cross linker

    CN101280069A

  • Amphiphilic block copolymer drug carrying micelle of K<+> responding type target intracellular drug releasing and preparation method thereof

    CN104906040A